Complexities in Colorectal Surgery Decision-Making and Management - Steele, Scott R.; Maykel, Justin A.; Champagne, Bradley J.; Orangio, Guy R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Complexities in Colorectal Surgery: Decision-Making and Management  provides a unique, modern, practical guide that covers the strategic evaluation, specific approaches, and detailed management techniques utilized by expert Colorectal Surgeons caring for patients with complex problems—whether they result from underlying colorectal disease or from complications arising from previous surgical therapy. The text is formatted as both a “how-to” manual as well as an algorithm-based guide allowing the reader to understand the thought process behind the proposed treatment strategies. By making use of evidence-based recommendations, each chapter will include not only diagnostic and therapeutic guidelines, but also a narrative by the author on his/her operative technical details and perioperative “tips and tricks” that they utilize in the management of these complex surgical challenges. This test includes chapters on the assessment of risk and nutritional intervention methods utilized to minimize perioperative complications. In addition, sections on medical and surgical therapies for abdominal, pelvic and anorectal disease are incorporated. Moreover, the technical challenges of managing complications resulting from the original or subsequent operations is addressed. The underlying focus throughout the text is to provide pragmatic and understandable solutions that can be readily implemented by surgeons of varying experience to successfully treat complex colorectal problems. The text also goes beyond the technical aspects of Colorectal Surgery and includes special sections highlighting the essence of a surgeon.  These include chapters describing the importance of the first encounter, building patient rapport, and demonstrating confidence and competence while showing humility and avoiding arrogance.  Additionally, aspects involving the medical-legal, ethical, and economic challenges confronting surgeons are covered.
Section I.  Preoperative -- 1. The First Encounter -- 2. Perioperative Risk Assessment -- 3. Perioperative Nutrition Support in Colorectal Surgery -- Section II.  The Abdomen -- 4. Diverticulitis: Beyond the Basics -- 5. Carcinomatosis: Cytoreduction and Heated Intra-peritoneal Chemotherapy (HIPEC) vs. Palliation -- 6. Metastatic colorectal cancer -- 7. Enterocutaneous fistulas -- 8. Enteroatmospheric Fistula -- 9. Technical Tips for Difficult Stomas -- 10. Continent ileostomies -- Section III.  The Pelvis -- 11. Rectal prolapse: current evaluation, management and treatment of a historically recurring disorder -- 12. Obstructive Defecation -- 13. Fecal incontinence -- 14. Local treatment of rectal cancer: TEMS versus TAMIS versus transanal excision) -- 15. Recurrent Rectal Cancer -- 16. The Approach to the Rectal Cancer Patient With a Suspected Complete Clinical Response – Selection of Patients to the Watch & Wait Strategy -- 17. Ileal Pouch Complications -- 18. The Failed Anastomosis -- 19. Pelvic bleeding -- Section IV.  Anorectal Disease -- 20. Hemorrhoidal Disease: Postoperative Complications -- 21. Fistula-in-ano -- 22. Anal Intraepithelial Neoplasia (AIN)/ High-Grade Squamous Intraepithelial Lesion (HSIL) -- 23. Chronic anal pain -- 24. Complex Pilonidal Disease: Point-Counterpoint Acute and Chronic Perieal Wound -- Section V.  Special Situations -- 25. Considerations in the Elderly -- 26. The Morbidly Obese patient -- 27. The Pediatric Patient -- 28. Functional Problems Following Colorectal Surgery -- 29. Short Bowel Syndrome -- 30. The Intraoperative Consult -- 31. Laparoscopic Complications -- 32. Laparoscopic, Robotics and Endoscopy -- 33. Technical Aspects -- 34. Colon and Rectal Trauma -- 35. When Vascular Surgery Calls -- Section VI.  Beyond the Operating Room -- 36. Facing our Failures -- 37. Teaching and Training for Laparoscopic Colorectal Resection -- 38. The Surgeon Investigator: Balancing Research and Clinical Practice -- 39. Medicolegal and Ethical Dilemmas -- 40. Economical Issues Impacting Surgical Care Delivery -- 41. Defining Competency and the Role of the Board -- 42. Knowing When to Say "When".
Keywords: Rectum—Surgery .; Surgical oncology; Surgery; Colorectal Surgery; Surgical Oncology; General Surgery